ANALISIS PERKEMBANGAN SOSIAL EMOSIONAL ANAK BERKEBUTUHAN KHUSUS (AUTISME) DI SKH 02 AL-IHSAN CILEGON - Nurul Wihdahtul Ummah; Yahdinil Firda Nadhirah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This article analyzes the socio-emotional development of children with special needs with autism in SKh 02 Al-Ihsan. With a focus on a child with the initials "D," the study includes observation of behavior, social interaction, and emotional management in the context of inclusive education. The methodology used includes direct observation, interviews with accompanying teachers, and analysis of child behavior data. The results showed that although "D" showed progress in academic understanding, he still faced challenges in social interaction and emotional management. The treatments applied, such as behavioral therapy and emotional support from the family, contribute positively to their social-emotional development. This article emphasizes the importance of a structured approach and ongoing support in improving the social and emotional skills of children with autism, and provides recommendations for more effective intervention programs in the school environment.